USING THE WHATSAPP APPLICATION IN ENGLISH LEARNING: CONCERNING STUDENTS' PERCEPTIONS AND ACADEMIC FLOW - Syahputra, Andi (IJEE (INDONESIAN JOURNAL OF ENGLISH EDUCATION), 2023)
ABSTRACTTechnological improvement has changed our educational systems from face-to-face learning to virtual learning, namely online learning. WhatsApp (WA) is an application that can be a medium to support students' English learning in a more accessible, flexible, and helpful way. The objectives of this study are to know the students' perceptions and academic flow of using the WA application in English learning, to understand the differences in their perceptions and academic flow based on their gender, age, and semester, and to know the correlation between both their perception and academic flow. The data was collected by quantitative research in survey research design. 172 State Islamic College students who studied English courses were selected randomly as the sample of this study. The data were gained through the questionnaire distributed online. Data were analyzed using descriptive statistics, Multivariate Analysis, and Correlation of SPPS. The findings revealed that the students positively perceive using WhatsApp applications in their English learning. Meanwhile, it is also an application that can directly impact their perceptions and academic flow. However, the correlation analysis found that students' perceptions do not have a significant relationship with the academic flow (r = .117, p > .05). ABSTRAKKemajuan teknologi telah mengubah sistem pendidikan kita dari pembelajaran tatap muka ke pembelajaran virtual, yaitu pembelajaran daring. WhatsApp adalah sebuah media yang dapat mendukung pembelajaran Bahasa Inggris siswa lebih mudah diakses, fleksibel, dan bermanfaat. Tujuan dari penelitian ini adalah untuk mengetahui persepsi dan kenyamanan akademik mahasiswa dalam penggunaan aplikasi WA pada pembelajaran Bahasa inggris, untuk memahami perbedaan persepsi dan kenyamanan akademik mahasiswa berdasarkan jenis kelamin, umur, dan semester, dan untuk mengetahui korelasi antara persepsi dan kenyamanan akademik mahasiswa. Metode penelitian yang digunakan adalah kuantitatif, dengan desain penelitian survey .172 mahasiswa  yang belajar mata kuliah Bahasa Inggris pada  Sekolah Tinggi Agama Islam Negeri dijadikan sampel penelitian ini secara acak. Data diperoleh melalui kuesioner yang disebarkan secara online. Analisis data menggunakan statistik deskriptif, Analisis Multivariat (MANOVA), dan korelasi yang dianalisis dengan SPPS. Temuan menunjukkan bahwa siswa memiliki persepsi positif terhadap penggunaan aplikasi WhatsApp dalam pembelajaran bahasa Inggris mereka. Sementara itu, WA juga merupakan aplikasi yang secara langsung dapat mempengaruhi persepsi dan kenyaman akademik mereka. Namun, Hasil analisis korelasi menunjukkan bahwa persepsi mahasiswa tidak memiliki hubungan yang signifikan dengan kenyamanan akademik (r = .117, p > .05).How to Cite: Syahputra, A. (2023). Using the Whatsapp Application in English Learning: Concerning Students' Perceptions and Academic Flow. IJEE (Indonesian Journal of English Education), 10(2), 261-277. doi:10.15408/ijee.v10i2.30217.